PENERAPAN E-CRM DALAM MENINGKATKAN OMZET PAKAIAN ANAK DAN DEWASA DI TOKO WULAN BUSANA - Ade Nurainun; William Ramdhan; Wan Mariatul Kifti wan mariatul (Jurnal Sistem Informasi dan Informatika (Simika), 2026)
The advancement of information technology has encouraged business actors, including retail stores such as Wulan Busana, to adopt more effective systems for managing customer relationships. One relevant solution is the implementation of Electronic Customer Relationship Management (e-CRM) to enhance customer loyalty and satisfaction. This study aims to design and implement a web-based e-CRM system at Wulan Busana store using the CodeIgniter framework. The method used is qualitative, with data collection techniques including observation, interviews, and literature review. The results of the study show that the e-CRM system helps the store manage customer data, monitor product stock, and carry out marketing activities in a more structured and efficient manner. The implementation of this system has proven to enhance interaction between the store and customers, accelerate responses to customer needs, and simplify promotional and sales evaluation processes. The system also has a positive impact on increasing customer loyalty and improving the store’s operational efficiency.